Photoluminescence study of Sr3Al32O51:Eu3+ phosphor for Solid state lighting applications - Bhelave, Samirkumar R.; Yerpude, A.N.; Dhoble, S. J. (Physics and Chemistry of Solid State, 2023)
Sr3Al32O51:Eu3+ phosphor prepared successfully by simple combustion method. Prepared matrix synthesized for different percentage of composition for rare earth Eu3+ = (0.5, 1.0, 1.5, 2.0 and 2.5). Photoluminescence property was taken for the given doped phosphor which shows the excitation peak at 395 nm and 466 nm respectively. Emission peak observed at 593 nm and 613 nm for excitation wavelength 395 nm and same emission peak observed for excitation wavelength 466 nm comparatively less intense than 395 nm. The phase of the synthesized phosphor confirmed by X-ray diffraction spectroscopy (XRD), Scanning electron microscopy (SEM), Photoluminescence (Pl) property shows that the given matrix is the one of the potential material which can be used for solid state lightening.